Does e-commerce drive rural households engaged in non-timber forest product operations to adopt green production behaviors?. (20th October 2021) - Li, Bowei; Xu, Caiyao; Zhu, Zhen; Kong, Fanbin
Abstract: The adoption of green production behaviors (GPBs) in non-timber forest product (NTFP) operations can improve soil quality and mitigate run-off and soil erosion in mountainous areas, which can support sustainable industry development. Selling NTFPs by e-commerce rather than traditional face-to-face trading can expand markets, prevent any high-quality product premium being lost to profit-seeking middlemen, and reduce the information asymmetry about the quality of products. Therefore, improvements in product quality can achieve a price premium, which can stimulate rural households engaged in NTFP operations (i.e. NTFP households) to adopt GPBs. This study uses survey data from 429 NTFP households in Zhejiang Province in southeastern China and econometric modelling to test whether e-commerce can foster NTFP households' adoption of GPBs The results show that the NTFP households are not commonly adopting GPBs but e-commerce does encourage their adoption of GPBs. In particular, e-commerce has a positive effect on the NTFP households' use of organic fertilizer and formula fertilizer (informed by soil testing). E-commerce has a negative effect on the households' use of high-toxicity pesticides and the frequency of using pesticides. Compared with small-scale NTFP households whose forestland size is lower than the mean of the total sample (i.e. <1.91 ha), e-commerce has a stronger effect on the adoption of GPBs by large-scale (i.e. >1.91 ha) NTFP households. The implication for policymakers from these findings is that e-commerce can be used to drive NTFP households to adopt GPBs in countries with free markets and functioning e-commerce platforms.